2010
DOI: 10.1128/jvi.02412-09
|View full text |Cite
|
Sign up to set email alerts
|

p62/Sequestosome-1 Associates with and Sustains the Expression of Retroviral Restriction Factor TRIM5α

Abstract: TRIM5 proteins mediate a potent block to the cross-species transmission of retroviruses, the most well known being the TRIM5␣ protein from rhesus macaques, which potently inhibits human immunodeficiency virus type 1 (HIV-1) infection. This restriction occurs at an early stage in the replication cycle and is mediated by the binding of TRIM5 proteins to determinants present in the retroviral capsid. TRIM5␣, as well as other TRIM family proteins, has been shown to be regulated by interferons (IFN). Here we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 48 publications
7
58
0
Order By: Relevance
“…We found that the attachment of K48-linked polyubiquitin was largely p62-dependent, suggesting that PV-bound p62 recruits E3 ligases other than K63-specific TRAF6. We identified Trim21 as such a PV-resident E3 ligase that is known to interact with p62 and to form K48-linked polyubiquitin chains (52)(53)(54). Further defining the function of PVassociated E3 ligases such as Trim21 will doubtlessly reveal novel insights into host defense mechanisms directed at vacuolar pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the attachment of K48-linked polyubiquitin was largely p62-dependent, suggesting that PV-bound p62 recruits E3 ligases other than K63-specific TRAF6. We identified Trim21 as such a PV-resident E3 ligase that is known to interact with p62 and to form K48-linked polyubiquitin chains (52)(53)(54). Further defining the function of PVassociated E3 ligases such as Trim21 will doubtlessly reveal novel insights into host defense mechanisms directed at vacuolar pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Excitation light was generated using the Insight SSI solid-state illumination module (Applied Precision, GE), and images were deconvolved with the SoftWoRx deconvolution software (Applied Precision, GE). Following deconvolution, images were quantified by Imaris (Bitplane) software using the Surfaces feature function, generating surfaces around red puncta, as described (77). Three-dimensional views of images were generated using Surpass mode of Imaris software (78).…”
Section: Methodsmentioning
confidence: 99%
“…3A); the known examples include TRIM5 (O'Connor et al, 2010), TRIM50 , TRIM55 (Lange et al, 2005;Pizon et al, 2013;Mandell et al, 2014), TRIM13 (Tomar et al, 2012), TRIM17 and TRIM49 (Mandell et al, 2014), TRIM21 , as well as TRIM76 (Blandin et al, 2013). Furthermore, p62 can colocalize with TRIM63 in the cytoplasm and with TRIM19 in the nucleus within the nuclear PML bodies (Pankiv et al, 2010), although this might not be restricted to the nucleus because TRIM19 functions in the cytoplasm as well (Lin et al, 2004;Dutrieux et al, 2015).…”
Section: Some Trims Bind To Slrsmentioning
confidence: 99%